(untitled) - Kushi, Michio (Tokyo, 1977)
Macrobiotics as traditionally interpreted from the time of ancient Greece, is the way of heath, longevity and happiness in the large sense, through the view and application of the cosmological understanding of life. Macrobiotics as currently presented throughout the world originated from the understanding of the oriental philosophy of life, namely the dualistic monism of yin and yang.Since the beginning of current education on the macrobiotic way of life, which is largely owed to George Ohsawa and his seniors and associates, numerous people have been turned from physical, mental, and spiritual unhappiness to health and freedom. This book is a simple introduction to the principles of health and happiness through the dietary approach based on the way of life according to the order of the universe, macrobiotics.
Keywords: Triết học, Châu Á,Philosophy, Asian